FOREIGN DIRECT INVESTMENT (FDI) AND EXPORT GROWTH CATALYSTS FOR ECONOMIC ADVANCEMENT IN UZBEKISTAN - Norimov, Islomiddin (International Journal of Business, Law and Political Science, 2024)
Foreign Direct Investment (FDI) and export growth are pivotal drivers of economic development, often serving as primary catalysts for economic advancement in emerging economies. In Uzbekistan, both FDI and exports play crucial roles in shaping the economic landscape, yet their interrelationship and impact on overall economic progress remain underexplored. Despite significant investments and export activities, there is limited empirical research evaluating how FDI and export growth specifically contribute to Uzbekistan's economic advancement and their combined effect on macroeconomic stability. This study aims to analyze the contributions of FDI and export growth to economic advancement in Uzbekistan, identifying the mechanisms through which these factors drive economic progress. The findings reveal that both FDI and export growth substantially contribute to economic advancement in Uzbekistan. Specifically, FDI has been instrumental in boosting industrial capacity and infrastructure, while export growth has enhanced the country's global trade integration and revenue streams. This research provides novel insights by highlighting the synergistic effects of FDI and export growth, demonstrating how their combined impact fosters economic stability and development in Uzbekistan. The results suggest that policy measures should focus on further integrating FDI and export strategies to maximize their economic benefits. Policymakers are encouraged to create an environment that attracts foreign investment while simultaneously promoting export competitiveness. Future research could explore sector-specific impacts and the long-term sustainability of these growth drivers in Uzbekistan's evolving economic context.